Golden Compass - Pullman, Philip
Published in 40 countries, Philip Pullman's His Dark Materials trilogy--The Golden Compass, The Subtle Knife, and The Amber Spyglass--has graced the New York Times, Wall Street Journal, San Francisco Chronicle, Book Sense, and Publishers Weekly bestseller lists. In 1996, The Golden Compass changed the face of fantasy publishing, and 2006 marks its 10 Year Anniversary--and an opportunity to celebrate with a deluxe hardcover. Pullman created new material just for this edition (archival documents, scientific notes and "found" letters of Lord Asriel) which has been illustrated and handlettered by renowned British artist Ian Beck and will be included in the back matter. The deluxe edition also features Pullman's own chapter opening spot art. A quality collectible--with the enticement of never-before-seen new material--for Pullman fans.
Appendix: Some papers from the Library at the Jordan College.
New! Lord Asriel's papers.
The golden compass ; The subtle knife ; The amber spyglass.
Keywords: det gode; England; Norge; Arktis